Foreign direct investment statistics : how countries measure FDI 2001 - International Monetary Fund.; Organisation for Economic Co-operation and Development (Washington, D.C. : International Monetary Fund ; OECD, 2003)
This report also provides information on the current practices regarding the statistical measurement of FDI of 61 countries, with the aim of improving users' understanding of the methodology applied for compiling the data.
Chiefly tables.
Includes bibliographical references.
oif 23/10/15
Loans
Keywords: Investments, Foreign; Investments, Foreign --- Statistical methods